Delay-dependent asymptotic stabilitzation for uncertain time-delay systems with saturating actuators - Liu, Pin-Lin (Zielona Góra: Uniwersytet Zielonogórski)
This paper concerns the issue of robust asymptotic stabilization for uncertain time-delay systems with saturating actuators. Delay-dependent criteria for robust stabilization via linear memoryless state feedback have been obtained. The resulting upper bound on the delay time is given in terms of the solution to a Riccati equation subject to model transformation. Finally, examples are presented to show the effectiveness of our result.
Keywords: stability; delay-dependency; time delay system; Riccati equation